Avaliação durante operação dos sistemas hidráulicos prediais e urbanos de conjuntos habitacionais de interesse social no município de Passo Fundo - Wunder, Laurita Regina (2006)
The habitacionals deficit for the low income populations has been a constant concern of the researchers of the constructed environment area, related mainly with studies on constructive techniques, land types of employed materials and its hydraulica systems. As well as the consideration of that these housings must be sustainable and in this point the hidric sustentability acquires important paper, but normally these habitations generate great ambient impacts where they are implanted. On this form the objective of this work was to carry through an evaluation during operation of the land and urban hydraulica systems of habitacionals sets of social interest implanted by the Municipal City Hall of Passo Fundo, in the period from 1966 to 2004. The evaluation was necessary for attainment of data on the used conception and project, materials and execution of the systems, as well as the form of use for the user, therefore it gives credit that only after the knowledge of the requirements and the behavior of the users of these systems is that it will be possible to consider alternative technologies of exploitation of the hidrics resources for this type of habitation and thus to reduce the generated impacts. The ADO of the systems was indicative, with the accomplishment of visits and interviews with the users; investigate, with the evaluation of the criteria of execution, maintenance, operation and use; and diagnostic with evaluations and related physical measurements with the answers of the users. The used technique made possible to prove the indifference in the conception and development of the projects, the low quality of the used materials and the execution of the land and urban hydraulica systems, as well as the maintenance lack what makes it difficult the adequate operation of the systems and becomes very difficult the application of alternative sources of supplying. It s also stands out that many of the problems are caused why the user doesn t know how to operate the systems, for this reason suggest that in this type of construction they are carried through, together with the construction and destination of the housings, programs of ambient education so that these users have conditions to give a better use for the habitations